Improvement of a direct solar dryer performance using a geothermal water heat exchanger as supplementary energetic supply. An experimental investigation and simulation study. (May 2019) - Sandali, Messaoud; Boubekri, Abdelghani; Mennouche, Djamel; Gherraf, Noureddine
Abstract: aiming to improve the thermal performance of a direct solar dryer, a new technique of heat supply was proposed and investigated using a double level tubular heat exchanger with geothermal water, constructed in LENREZA laboratory. The heat exchanger was placed deliberately above the absorber plate facing the holes so as to enable the air penetration. The temperature of the circulating water was set to 70 °C analogically to that of geothermal water in southern regions of Algeria. The experiment was carried out in LENREZA laboratory, (laboratory of development of new and renewable energy in arid and Saharan zones), University of Ouargla, Algeria. Moreover, numerical simulation was carried out and results were compared with the experimental. The findings showed that the integration of heat exchanger improves significantly the solar dryer performance. By using heat exchanger, the lowest drying air temperature was found to be 46 °C, while the highest one was 58 °C. After sunset and throughout the night, the drying air temperature remains important and almost steady with an average value of 46 °C. The integration of the heat exchanger ensures the continuity of drying process at the night and even during cloudy days. Highlights: Improvement of solar drying systems is very important in drying technology. A new technique of improvement of a direct solar dryer performance using geothermal water heat exchanger has been studied and discussed. With integration of heat exchanger, the smallest obtained value of drying air temperature was found 46 °C, while the highest one was 58 °C. The integration of the heat exchanger ensures the continuity of drying process at the night and even during the cloudy days.